Trends in outside support for insurgent movements - Byman, Daniel, 1967- (Online Rand research documents., 2001)
This report assesses post-Cold War trends in external support for insurgent movements. It describes the frequency that states, diasporas, refugees, and other non-state actors back guerrilla movements. It also assesses the motivations of these actors and which types of support matter most.